2007
DOI: 10.1177/004908570703700402
|View full text |Cite
|
Sign up to set email alerts
|

Women and poverty: Rural-urban dimensions

Abstract: This paper focuses on the gender dimensions of poverty with analysis of rural and urban area specific variations. What are the implications of poverty on women's lives? Is the impact of poverty on women distinct? In what ways are poor women more vulnerable? So far, the focus has been on rural poverty, with more recent shifts towards the concerns of urban poor. Is urban poverty a spillover of rural poor through migration? What are the characteristic features of urban poverty and how do they differ from rural po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…They experience multiple forms of deprivations such as women‐specific ill health, low levels of education and lack of decision‐making power (Chant, 2007). Furthermore, women are alienated from different social and economic rights tailored towards their needs, such as access to credit, land, and/or other productive assets (Rustagi, 2007; Tacoli, 2012). In literature, this gender dimension of poverty is called “feminization of poverty.” Feminization of poverty is a notion that women constitute the poorest of the poor and disproportionate numbers of women are overburdened by poverty and its calamities (Chant, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They experience multiple forms of deprivations such as women‐specific ill health, low levels of education and lack of decision‐making power (Chant, 2007). Furthermore, women are alienated from different social and economic rights tailored towards their needs, such as access to credit, land, and/or other productive assets (Rustagi, 2007; Tacoli, 2012). In literature, this gender dimension of poverty is called “feminization of poverty.” Feminization of poverty is a notion that women constitute the poorest of the poor and disproportionate numbers of women are overburdened by poverty and its calamities (Chant, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on feminization of poverty were initially constrained by unavailability of data. In the 1980s, however, scholars suggested that relative vulnerabilities of female‐headed households (FHHs) can be used as a proxy for the multifaceted poverty faced by women (Rustagi, 2007; Tacoli, 2012). FHHs have, therefore, become a focus of economic and social researches.…”
Section: Introductionmentioning
confidence: 99%
“…According to a study, conducted by the Planning commission expert group, the annual compound growth estimate is relatively high for the destitute women (Rustagi, P., 2007). To fully understand the different facets of poverty and for getting potential gender-sensitive solutions, the policy makers need to develop an index which takes into account aspects like health, education, employment etc.…”
Section: Multidimensional Approach To Measure Of Povertymentioning
confidence: 99%
“…The UGC (University Grants Commission, Government Ministry), in partnership with the Tata Institute of Social Sciences-School of Vocational Education (TISS-SVE), has composed a work coordinated training model to offer an assortment of professional courses (Rustagi, P., 2007). The TISS-SVE initiative offers skill-set building and training programs in various sectors, all in association with businesses.…”
Section: Tiss Vocational Coursesmentioning
confidence: 99%
See 1 more Smart Citation